Analisis Perbandingan Perbaikan Kualitas Citra Pada Motif Batik Dengan Konsep Deteksi Tepi Robert, Sobel, Canny Menggunakan Metode Morfologi - Muhammad Abrar Masril; Yuhandri; Jufriadif Na’am (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Image results from quality edge detection are not optimal. From these problems a method is needed to improve the image quality of edge detection. The method used is Dilation Morphology on the results of edge detection of batik patterns. The results of testing the improved image quality of edge detection 10 batik patterns using Dilation Morphology show that Canny operators are able to produce very high accuracy from operators Robert and Sobel, with the percentage of Canny operators is 80%. While Robert operators with a percentage of 40% and Sobel operators 60%. The application of Dilation Morphology to operators Robert, Sobel and Canny can improve image quality of edge detection and improve accuracy in batik patterns.